Konteks Sistem Sekunder Di Situs Cabean Kunti, Boyolali (Pandangan Masyarakat dan Dampaknya pada Kelestarian Situs) - Sugeng Riyanto (Berkala Arkeologi, 2005)
The secondary system context is the BCB (heritage) that applies in today's society's life system. This phenomenon becomes interesting because the "utilization" of BCB by the community today is different from the "utilization" referred to in the concept of Cultural Resource Management (CRM). The first may be categorized as traditional use, while the second (CRM) is a planned use (managed) with a broader function, for example as a tourist object (economics), education (ideology), or for the development of science (academics).